The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3920/bm2020.0146
|View full text |Cite
|
Sign up to set email alerts
|

Heat inactivation partially preserved barrier and immunomodulatory effects of Lactobacillus gasseri LA806 in an in vitro model of bovine mastitis

Abstract: Probiotics could help combat infections and reduce antibiotic use. As use of live bacteria is limited in some cases by safety or regulatory concerns, the potential of inactivated bacteria is worth investigating. We evaluated the potential of live and heat-inactivated Lactobacillus gasseri LA806 to counteract Staphylococcus aureus and Escherichia coli infection cycles in an in vitro model of bovine mastitis. We assessed the ability of live and inactivated LA806 to impair pathogen colonisation of bovine mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Heat inactivation can affect the surface properties and structures of bacterial cells, which can lead to changes in their adhesion ability to host cells ( 38 ). It has been reported that heat inactivation of Escherichia coli and Staphylococcus aureus caused a significant decrease in its adhesive properties ( 39 ). E.coli and S.aureus were able to adhere more strongly to surfaces after being exposed to low-temperature inactivation compared to high-temperature inactivation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heat inactivation can affect the surface properties and structures of bacterial cells, which can lead to changes in their adhesion ability to host cells ( 38 ). It has been reported that heat inactivation of Escherichia coli and Staphylococcus aureus caused a significant decrease in its adhesive properties ( 39 ). E.coli and S.aureus were able to adhere more strongly to surfaces after being exposed to low-temperature inactivation compared to high-temperature inactivation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another example includes a study by Jorjão et al (2015) who reported that heat-killed Lactobacillus rhamnosus ATCC7469 cells were able to stimulate mouse macrophages to produce cytokines including IL-4, IL-6, IL-10, IL-12, among others. In other bovine mastitis-related studies, Blanchet et al (2021) demonstrated the immunomodulatory efficacy of heat-killed Lactobacillus gasseri LA806 in the process of impairing E. coli and S. aureus colonization of bovine mammary epithelial cells (bMEC) in in vitro models. A separate study by Fukuyama et al (2020) , also reported the immunomodulatory efficacy of LAB strains in stimulating Toll-like receptor-mediated inflammatory responses in in vitro bMEC models.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of total RNA of Caco2, HT29-MTX-E12, and M cells from one hand, and THP1 cells from the other hand, was performed as previously described [ 27 ]. Gene expression analysis was performed with the SmartChip Real-Time PCR System technology and with the 384-well plate PCR system for genes with detectable, but low, expression using the SmartChip system (cycle threshold (Ct) >28) ( Table S3 ).…”
Section: Methodsmentioning
confidence: 99%